About the Places Where Ecotourism can be Developed in the Territory of Alat District of Bukhara Region of the Republic of Uzbekistan. - Usmonov Erkin Toyirovich; Rakhmonov Gayrat Fazliddinovich (Genius Journals, 2022)
This article states that it would be expedient to establish health-improving sanatoriums for human health on the shores of Dengizkul and Shurkul, and in the future to establish seasonal and non-seasonal ecotourism zones for the rational use and preservation of natural resources.
Keywords: Seawater; saltwater; ecotourism; salt sand